CLINICAL EFFICACY OF NON-HORMONAL METHODS OF THERAPY IN PERIMENOPAUSAL WOMEN - T. V. Ovsyannikova; I. O. Makarov; I. A. Kulikov (IRBIS LLC, 2016)
This article presents a contemporary look at the causes of the appearance of hot flashes in menopausal women, and the possibility of non-hormonal methods of correction, based on indications and contraindications.